A Review on Carbon Fiber Reinforced Polymer as Wrapping Structures For Pipeline - Letchumanan, S. M.; Arifin, A. M. T.; Ismail, A. E.; Taib, I. (International Journal of Integrated Engineering, 2023)
To maintain the continuous product flow in the pipe, the durability of the pipe structure is achieved through pipe insulation. The composite material will be used as the main material, since it may have the combined characteristics of the constituents or have substantially different properties than the individual constituents. Replacing the damaged pipe with a new one will not only consume high cost but also will create a complication for product flow. As to alleviate such situations this research focusses on using the carbon fiber as the wrapping material. To identify the suitable design and optimization of laminated carbon fiber on piping systems, the defect, leakage and imperfection on pipe should be identified. The effect of different laminate optimization through Classical Laminate Theory CLT and experimental data too need to be considered as it changes the mechanical properties of the composite material. The microstructure of the composite too will be validated as an extra reference for the theoretical and experimental data on its effect in the microstructure after the loading